The compassionate connection : the healing power of empathy and mindful listening - Rakel, David; Golant, Susan K. (W.W. Norton & Company, 2018)
Draws on a range of disciplines to outline the concept of bio-psycho-spiritual authentic awareness and how to strengthen empathy bonds with others to promote healing and overall wellness.